MELESTARIKAN TRADISI KERINCI MELALUI SENI REFLEKSI NILAI DALAM NANJOAK UMOH - Indah Bunga Lestari; Maryati, Eva; Aisayh, Siti; Putri, Fania Maidila; Putri, Kinanti Rizki; Fithri, Wardatul; Yunizha, Thera Dies; Irfan; Falah, Andy Makarim; Nuraini; Puspita, Rema; Gesta, Lara; Yanti, Lusi Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Tradition is an integral part of a society’s identity, including the Kerinci community, which is rich in culture and local values. In the face of globalization, efforts to preserve traditions have become increasingly important. This research focuses on the role of the Nanjoak Umoh ritual as a reflection of local values and an effective means of preserving the cultural heritage of Kerinci. The primary aim of this study is to identify the values embedded in the Nanjoak Umoh ritual, to analyze the role of this cultural practice in preserving Kerinci’s tradition, and to provide recommendations for its development. A qualitative approach was used, employing participatory observation, in-depth interviews with local leaders, artists, and community members, as well as document analysis. The findings suggest that Nanjoak Umoh plays a significant role in cultural preservation through the use of symbolic elements such as Batang Puar and rituals that foster social solidarity. It also strengthens the sense of community identity and serves as a moral lesson for younger generations. The research concludes that for the tradition to thrive, it requires further documentation, integration into local educational curricula, and digital promotion to expand its reach. These efforts will help ensure that the tradition is passed down to future generations and remains relevant in modern times.